Penguatan Kearifan Lokal dalam Pembelajaran melalui Pengembangan Bahan Ajar Pendidikan Agama Islam - Syahrul Riza (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This article examines the strengthening of local wisdom in learning Islamic Religious Education in schools. This research leads to the development of PAI teaching materials associated with local wisdom. The purpose of this research is to find and research about PAI teaching materials that are applied by juxtaposing or linking them with local wisdom. In the process, this research does not direct the learning of Islamic Religious Education in the qualitative and quantitative domains or in combination, but this learning can use one or even both in its learning methodology. This study discusses the application of learning that leads to the development of PAI teaching materials by looking at Islamic values and local wisdom. This can be referred to as the result of observing habits that are taught and practiced in the learning process activities at school.